Influence of in situ postweld heat treatment on microstructure and failure behavior of dual-phase steel resistance spot weld - Soomro, I.A. (Springer Science and Business Media Deutschland GmbH, 2021)
The present study aims to investigate the effect of in situ postweld heat treatment (PWHT) on microstructure, tensile shear properties, failure mode, and hardness distribution of resistance spot weld of dual-phase (DP590) steel. Tensile shear properties were evaluated in terms of peak load and failure energy. Results showed that welds subjected to high heat input in situ PWHT via double-pulse RSW process exhibit higher peak load and failure energy compared with conventional single-pulse weld. The improvement in mechanical performance is attributed to increased weld nugget size and the transition of failure mode from interfacial fracture mode to pullout fracture mode. Moreover, it was also found that increasing the tensile shear test velocity from 1.6 Ã 10â4 msâ1 (quasi-static) to 8.3 Ã 10â3 msâ1 for low-dynamic increased the peak load and failure energy of the weld. Â© 2021, The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature.